Thermal Performance Study of a Cement-Based Mortar Incorporating EPS Beads - Horma, Othmane; Charai, Mouatassim; El Hassani, Sara; El Hammouti, Aboubakr; Moussaoui, Mohammed A.; Mezrhab, Ahmed (Frontiers in Built Environment, 2022)
Recycling plastic waste has been one of the most significant challenges in the recent decade. The reuse of one of the most produced cellular plastics (i.e. EPS) within a conventional construction binder can contribute, simultaneously, to waste elimination and improving energy performances of the building envelopes. This work investigates the recycling of expanded polystyrene (EPS) waste within a cement-based matrix. The aim is to develop a lightweight, energy-efficient composite for eco-construction. Portland cement was mixed with a small amount of gypsum (4 wt%) before adding EPS aggregates ranging from 0-0.6 wt%. The thermal properties were determined using two different non-destructive methods, the transient plane source technique (Hot Disk Method) and the Flash method. The experimental results showed a remarkable decrease of 54%, 12%, and 36% in thermal conductivity, thermal diffusivity, and density, respectively. These results indicate the improvement of thermal resistance of EPS-cement-gypsum- mixes. In addition, water absorption and compressive tests revealed that cement-based composites containing EPS beads have improved durability and can be used for structural and insulation purposes. Finally, Numerical results indicated that energy savings of up to 18% may be achieved by applying produced waste-based mortar, underscoring the promise of using this product for building energy efficiency benefits.